Effect Of Different Methods Of Preservation On The Quality Of Cattle And Goat Meat - Faisal, S Bin; Akhter, A; Hossain, MM (Bangladesh Journal of Animal Science, 2012)
The study was conducted to evaluate the effect of drying, curing and freezing on the quality of cattle and goat meat collected and designed as. Cattle and goat meat samples were: dried cattle meat with salt (M1), dried cattle meat without salt (M2), dried goat meat with salt (M3), dried goat meat without salt (M4), cured cattle meat with salt (M5), cured cattle meat with sugar (M6), cured goat meat with salt (M7), cured goat meat with sugar (M8), frozen cattle meat with salt (M9), frozen cattle meat without salt (M10), frozen goat meat with salt (M11) and frozen goat meat without salt (M12) and analyze on every 30 days interval up to the period of 120 days. Chemical constituents of meat samples (dry matter, protein, ash and fat) decreased gradually with the increasing of storage time, but dry matter increased gradually during freezing period. The initial dry matter, ash, protein and fat contents of the samples (M1, M2, M3, M4, M5, M6, M7, M8, M9, M10, M11, M12) ranged from 81.26 to 98.50%, 15.01 to 22.46%, 60.28 to 77.30% and 3.04 to 6.70% and final value were ranged from 80.03 to 88.12%, 10.92 to 18.50%, 57.98 to 68.93% and 2.50 to 5.90%, respectively. The elapse of storage time quality parameters of meat samples degraded significantly (P<0.05 to 0.01). Quality parameters also varied among the samples (P<0.05 to 0.01). Considering fat and protein value of cattle and goat meat, salt drying and sugar curing were better than other preservation methods. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9916 BJAS 2009; 38(1-2): 86-91